2 x + y = 9 Subtract 2x to both sides
2 x + y - 2 x = 9 - 2 x
y = 9 - 2 x
y = - 2 x + 9
Now put x values in this formula
x = - 3
y = - 2 x + 9 = - 2 * ( - 3 ) + 9 = 6 + 9 = 15
x = - 3 , y = 15
x = 1
y = - 2 x + 9 = - 2 * 1 + 9 = - 2 + 9 = 7
x = 1 , y = 7
x = 4
y = - 2 x + 9 = - 2 * 4 + 9 = - 8 + 9 = 1
x = 4 , y = 1
x = 5
y = - 2 x + 9 = - 2 * 4 + 9 = - 10 + 9 = - 1
x = 5 , y = - 1
x = - 1
y = - 2 x + 9 = - 2 * ( - 1 ) + 9 = 2 + 9 = 11
x = - 1 , y = 11
complete table for the following equation
2x+y=9
x y
-3
1
4
5
-1
2 answers
x = 5
y = - 2 x + 9 = - 2 * 5 + 9 = - 10 + 9 = - 1
x = 5 , y = - 1
y = - 2 x + 9 = - 2 * 5 + 9 = - 10 + 9 = - 1
x = 5 , y = - 1